Pengaruh Pembelajaran Berbasis Masalah Terhadap Kemampuan Komunikasi dan Berpikir Kritis Peserta Didik Kelas X di UPTD SMAN 1 Mamuju - Sarinah Sarinah; Helmi Helmi; Pariabti Palloan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Communication and critical thinking skills are essential competencies in 21st-century learning, particularly in physics education, which requires analytical ability, scientific argumentation, and problem-solving skills. However, teacher-centered learning practices often limit students' involvement in constructing concepts and expressing ideas effectively. This study aimed to analyze the effect of Problem-Based Learning (PBL) on the communication and critical thinking skills of tenth-grade students at UPTD SMAN 1 Mamuju. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research sample consisted of 36 students in the experimental class and 35 students in the control class selected through purposive sampling. Data were collected using communication skill tests, critical thinking tests, and learning implementation observation sheets, then analyzed using descriptive statistics, Independent Sample T-Test, and N-Gain analysis. The results showed that PBL improved students' communication skills with an N-Gain score of 0.40 and critical thinking skills with an N-Gain score of 0.52, both categorized as moderate improvement. Hypothesis testing showed a significant difference between the experimental and control classes with a significance value of 0.000. These findings indicate that problem-solving activities, discussions, and investigations in PBL encourage students' active participation in learning. In conclusion, PBL is an effective learning model for improving students' communication and critical thinking skills in physics learning.